An Application of Behavioral Activation Therapy for Major Depressive Disorder in the Context of Complicated Grief, Low Social-Economic Status, and Ethnic Minority Status. (August 2015) - Vergara-Lopez, Chrystal; Roberts, John E.
Behavioral activation (BA) has been shown to be an effective treatment for depression, especially for severe and/or chronic depression; however, there is little empirical guidance on how BA can be effectively utilized to treat chronic Major Depressive Disorder (MDD) in the context of complicated grief, low socioeconomic status, and ethnic minority status. This case study focuses on the treatment of Ms. X, a 51-year-old African American woman with chronic depression that was exacerbated by complicated grief. This case describes an effective course of a standard BA protocol for MDD in the context of complicated grief, low socioeconomic status, and ethnic minority status and illustrates how a BA protocol can be applied while incorporating important cultural considerations.